ABO Blood Groups Distribution and Cardiovascular Major Risk Factors in Healthy Population - AA Abdollahi; M Qorbani; A Salehi; M Mansourian (Tehran University of Medical Sciences, 2009)
"nBackground: This study was designed to investigate whether there was an association between ABO blood groups and cardiovascular risk factors in healthy population."nMethods: In this cross-sectional study, risk factors screening for cardiovascular disease(CVD) on 5000 healthy persons of Golestan Province, northern Iran, in 2005 was estimated by a questionnaire that included age, sex, physical activity, smoking status, blood group type (if they had blood laboratory tests), weight, height, blood pressure and family history of coronary artery disease (CAD). Data were analyzed with SPSS version 11.5 and by using Chi Square and ANOVA tests. A p-value less than 0.05 were considered as statistically significant."nResults: Amongst 5000 subjects, 2920 had blood laboratory tests and their types of blood group were known. Of the total of 2920, 57.4% were male, 70% were inactive, 14% were smoker, 25% were hypertensive, 23% obese, 21% had family history of CAD and mean age was 41.52±12.317. Blood group O(32.9%), A(30.1%), B(23.3%) and AB(13.7%), respectively had most frequency. Amongst cardiac risk factors, only frequency of family history of CAD in individual with different blood groups was different (P< 0.01) and individual with A blood group reported more family history of CVD versus other blood groups."nConclusion: Amongst cardiovascular risk factors, only family history of CAD had significant relation with ABO.